Competition between vinylidene rearrangement and 1, 2-insertion of carbon-disubstituted internal alkynes at a Cp*Ir(iii) complex. Issue 40 (2nd September 2015) - Ikeda, Yousuke; Kodama, Shintaro; Tsuchida, Noriko; Ishii, Youichi
Abstract : Competition between vinylidene rearrangement/1, 1-insertion and 1, 2-alkyne insertion into the Ir–Ar bond of [Cp*Ir(ppy-F4 )] + was observed on reaction with diarylacetylenes. The former process afforded the 9-membered iridacycle via the subsequent 1, 4-Ir migration. Abstract : Competition between vinylidene rearrangement/1, 1-insertion and 1, 2-alkyne insertion into the Ir–Ar bond of [Cp*Ir(ppy-F4 )] + was observed on reaction with diarylacetylenes. The former process afforded the iridacycle2 via the subsequent 1, 4-Ir migration, whereas the latter led to the pyridoisoquinolinium complex4 . Detailed analysis revealed that4 isomerizes to2 by heating at 50 °C.